OCCURRENCE OF A LARGE SHOAL OF JAVANESE COWNOSE RAY, RHINOPTERA JAVANICA MULLER & HENLE IN TOE BAY OF BENGAL OFF MADRAS - Srinivasarengan, S (Indian Journal of Fisheries, 2011)
The Javanese Cownose Ray, Rhinoptera Javanica Muller & Henle is known to congregate in large shoals and enter the coastal waters during the breeding season. Shipley and Hornell (1906) have reported the capture of 7000 individuals in a single net in Dutch Bay, Ceylon during the pearl fishery season of 1889. The occurrence of such shoals consisting of 500 to 4000 rays have been recorded in the Gulf of Mannar in India during the months of December-February (James 1962, 1970). Such shoals of R. javanica had not been recorded in any other area along the Indian coast.